Carbolithiation of Chloro‐Substituted Alkynes: A New Access to Vinyl Carbenoids. Issue 33 (17th July 2014) - Lhermet, Rudy; Ahmad, Maha; Fressigné, Catherine; Silvi, Bernard; Durandetti, Muriel; Maddaluno, Jacques
Abstract The intramolecular carbolithiation of a series of chloro‐substituted alkynes leads to exocyclic alkylidene carbenoids of which both nucleophilic and electrophilic characters can be drove. A sole stereoselective 5‐exo‐dig addition takes place, probably because of a strong and persisting Li–Cl interaction arising before the transition state.